2007
DOI: 10.1002/ijc.22730
|View full text |Cite
|
Sign up to set email alerts
|

Obesity does not predispose to more aggressive prostate cancer either at biopsy or radical prostatectomy in European men

Abstract: Many investigators suggested that obesity predisposes to adverse prostate cancer characteristics and outcomes. We tested the effect of obesity on the rate of aggressive prostate cancer at either prostate biopsy or radical prostatectomy (RP). Clinical and pathological data were available for 1,814 men. Univariable and multivariable logistic regression models addressed the rate of high grade prostate cancer (HGPCa) at either biopsy or final pathology. Clinical stage, prostate-specific antigen (PSA), percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
3
34
3
Order By: Relevance
“…Recent study results from the Shared Equal Access Regional Cancer Hospital (SEARCH) database found that obesity is a risk factor for aggressive prostate cancer regardless of race (4). On the other hand, a cross-sectional evaluation of 1,814 prostate cancer patients in Germany suggested that obesity does not predispose to more aggressive prostate cancer either at biopsy or at radical prostatectomy (5). Similarly, a clinical cohort of 2,687 patients who underwent treatment for low and intermediate grade of prostate cancer found no association between BMI and biochemical failure after at least of 2-year follow-up (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recent study results from the Shared Equal Access Regional Cancer Hospital (SEARCH) database found that obesity is a risk factor for aggressive prostate cancer regardless of race (4). On the other hand, a cross-sectional evaluation of 1,814 prostate cancer patients in Germany suggested that obesity does not predispose to more aggressive prostate cancer either at biopsy or at radical prostatectomy (5). Similarly, a clinical cohort of 2,687 patients who underwent treatment for low and intermediate grade of prostate cancer found no association between BMI and biochemical failure after at least of 2-year follow-up (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies addressing this issue using BMI estimates indicate contradictory results. Some prostate biopsy [31][32][33][34] and prostatectomy series 19,35,36 have shown more aggressive features among obese patients, whereas no such effect was observed by other authors (Table 5).…”
Section: Discussionmentioning
confidence: 83%
“…It is interesting to note that in our patients, an association with more aggressive characteristics (GS and NCCN prostate-risk group) was observed for SAT and VAT, but not for BMI. This might explain why some previous studies, 31,33,34,36 which analyzed only the influence of BMI and not of fat distribution on adverse pathologic features, failed to find such an association ( Table 5). The results of the current study highlight the advantage of using more sophisticated anthropometric measures of abdominal adiposity than simple BMI to evaluate the influence of obesity in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, obesity does not change the ability to identify those who may harbor a high grade tumor at radical prostatectomy. In consequence, the consideration of obesity might be omitted from CaP detection or diagnostic schemes [25].…”
Section: Discussionmentioning
confidence: 99%